Preferensi Sumber Informasi Inovasi Pengolahan Kotoran Ternak Menjadi Kompos pada Kelompok Peternak Sapi Potong di Kabupaten Bantul - Emiliana Anggriyani; F Trisakti Haryadi; Suharjono Triatmojo (Universitas Sebelas Maret (UNS), 2012)
The aim of this study was to analyze the sources of information of innovation in processing manure into compost. The respondents used in this study were the members of Sido Rejo and Sido Mulyo groups in Bantul who had already obtained information about the innovation of compost. This research was conducted by census through interviews of the object of research to obtain primary data. The preference of the information source of compost innovation was analyzed by descriptive method.The results of the research showed that most respondents from Sido Rejo and Sido Mulyo group preferred the personal information source. The study came to a conclusion that the personal information source was preferred by most respondents from Sido Rejo and Sido Mulyo groups.Key words: preference, source of information, innovation, compost